Product Design Enhancing Environmental Perception and Encouraging Behavioural Change: Eco-Information the Relationship of Design Styles and Users Emotions - Chanon Tunprawat; Yanin Rugwongwan; Wichitra Singhirunnusorn (My University, 2017)
This research is to develop the products that can communicate environmental information to the user. The study investigated design styles of eco-information and impact on user’s emotions which can be used as data for product design enhancing environmental perception and encouraging behavioural change. The research aimed to 1) study design styles of eco-information and impact on user’s emotions 2) analyse the relationship of design styles and impact on user’s emotions effective in promoting environmental behaviour change. Ten-second video clips of seven design styles were presented through a computer and a projector and perception evaluation forms were employed. The sample included 60 students from the Faculty of Architecture and Design, Rajamangala University of Technology Phra Nakhon, Bangkok, Thailand. The results showed that the most effective design style could encourage emotions in the aspects of interest, excitement and preference. This study found that using living creatures to encourage emotions was the most effective attribute. Additionally, giving detailed information through the use of texts and graphs could encourage effectiveness in promoting behavioural change towards energy and resource consumption.
Keywords: Creatures; Color perception and design